Assessing the knowledge, attitudes, and practices (KAP) of dengue in Thailand: a systematic review and meta-analysis - Julia Crowley; Bowen Liu; Hanan Jan (Archives of Public Health)
Abstract Aim Dengue cases are on the rise in Thailand, coinciding with increases in flooding events. Studies pertaining to public knowledge, attitudes, and practices (KAP) of dengue prevention have frequently been used to better understand the public’s needs towards dengue. While these studies were conducted in different settings, it is necessary to initiate a systematic review and meta-analysis of relevant studies. Subjects and method We conducted a systematic review and meta-analysis of prior studies in Thailand that assessed the KAP towards dengue. Eligibility criteria were established and independently used by reviewers to select nine studies for the systematic review and three for the meta-analysis. Collectively, the nine studies included 3,058 individuals and 2,519 households. Results The overall estimate of the proportion of participants with good knowledge of dengue prevention is 35% (95% CI: 14-59%), suggesting the majority of the population in Thailand had low levels of knowledge towards dengue. The poor levels of practice in Thailand were also observed and confirmed for the majority of the population by meta-analysis, with the pooled estimate of the proportion of participants with good practice of dengue prevention being 25% (95% CI: 22-27%). In contrast, most of the studies included in the systematic review reported positive attitudes towards dengue prevention, and this finding was also affirmed by the meta-analysis, as the pooled estimate of the proportion of positive attitudes towards dengue prevention is 61% (95% CI: 43-77%). Conclusion Despite good attitudes towards dengue prevention, poor knowledge and poor practices predominate, highlighting the need for enhanced public health campaigns to educate the public on dengue risks and prevention methods.